Structurafand metabolic peculiarities of erythrocytes in patients with systemic vasculitis - M M Faslyev (Научно-практическая ревматология, 2004)
Obyective. To assess of functional , structural and metabolic changes of RBC in patients with systemic vasculitis. To estimate influence of RBC abnormalities on blood viscosity and hemostasis. Materials and methods. Blood samples of 75 pis with Henoch-Schonlein Purpura (HSP) and 15 pts with microscopic polyarteritis (MPA) were tested. The levels of ATP transporting enzymes and lipid peroxide oxidation (LPO) in erythrocyte's membranes were assessed. The degree of erythrocyte membrane stability was estimated by test of osmotic and acidic membrane resistance. Results. Suppression of Na +, K +, Ca + activated ATP transporting enzyme in pts with MPA and renal form of HSP was found. This group of patients was also characterized by LPO activation, decreased osmotic and their acidic resistance of erythrocytes and their marked hyperaggregation. Conclusion. The assessment of structural and functional changes of erythrocytes helps to estimate abnormalities of blood viscosity and wo adjust management and predict prognosis in pts with systemic vasculitis.